Metabolomic Profiling Reveals New Insight of Fowl Adenovirus Serotype 4 Infection - Ma, Haiying; Niu, Yujuan (Frontiers in Microbiology, 2022)
Highly pathogenic fowl adenovirus serotype 4 (FAdV-4) is the causative agent of hydropericardium syndrome (HPS), which is characterized by pericardial effusion and hepatitis, and is one of the foremost causes of economic losses to the poultry industry over the last 30 years. However, the metabolic changes in cells in response to FAdV-4 infection remain unclear. In order to understand the metabolic interactions between the host cell and virus, we utilized ultra-high-performance liquid chromatography/quadrupole time-of-flight tandem mass spectrometry to analyze the metabolic profiles with hepatocellular carcinoma cell line (LMH) infected with FAdV-4. The results showed that FAdV-4 could restore metabolic networks in LMH cells and tricarboxylic acid cycle, glycolysis, and metabolism of purines, pyrimidines, alanine, aspartate, glutamate, and amino sugar and nucleotide sugar moieties. Moreover, FAdV-4 production was significantly reduced in LMH cells cultured in glucose or glutamine-deficient medium. These observations highlighted the importance of host cell metabolism in virus replication. Therefore, similarities and disparities in FAdV-4-regulation of the metabolism of host cells could help improve targeted drug and reduce infection.